Analisis Stabilitas Lereng Terhadap Longsoran Pada Titik Rencana Lubang Bukaan THC 04 CV. Tahiti Coal, Sangkar Puyuh, Sawahlunto, Sumatera Barat. - Pandu Poernaddie Iswara; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Based on observations made on the slopes in the THC 04 CV. Tahiti Coal, found rock slope which has a height of 30 meters, slope angle is 80° and has many weak plane structures that can cause landslides. Therefore it is necessary to analyze the rock mass and the stability of the slope. From the analysis that has been done, the rock mass classification value is 53, with medium quality and safety factor value at saturation condition is 1,141, original condition is 1,380, dry condition is 1,443. So it can be concluded that the slope condition is stable, except when saturated. Therefore, improvements need to be made in the form of reducing the slope angle to 66º and 67°, so that the value of the saturated slope safety factor changes to 1.256.Keywords: Open pit, slope, landslide, rock mass, safety factor.